Benefits of the state acres for wildlife enhancement practice for bird populations in Kansas - Thomas, Alaina D. (Kansas State University, 2014)
Grassland birds have experienced population declines worldwide from habitat degradation caused by conversion to agriculture and recent intensification of land use, including increased use of fertilizer, fossil fuels, and irrigation. The U.S. Department of Agriculture, Conservation Reserve Program (CRP) includes initiatives targeting wildlife enhancement to mitigate ongoing declines in grassland bird populations. The newest CRP practice, State Acres for Wildlife Enhancement (SAFE), was designed to restore vital habitats for high priority wildlife species throughout the United States. Our objective was to assess the potential benefits of SAFE for upland gamebirds and grassland songbirds in Kansas. We monitored lands enrolled in SAFE to estimate bird density based on field scale and landscape scale characteristics. Our study was conducted in three ecoregions: Smoky Hills (4 counties), Flint Hills (3 counties), and the High Plains (3 counties). We surveyed 121 SAFE fields and 49 CRP fields from 2012 – 2013. Northern Bobwhite density was negatively associated with percent litter within survey fields. Ring-necked Pheasant density differed among ecoregions, and was positively associated with percent bare ground in the High Plains, but negatively associated with field age in the Smoky Hills. Mourning Dove density differed among ecoregions, and was negatively associated with percent forb in the High Plains, and positively associated with percent grassland in the Smoky Hills. In the Flint Hills, Mourning Doves were negatively associated with CRP fields and large fields. Brown-headed Cowbirds were positively associated with percent forbs. Amount of CRP surrounding survey locations was positively associated with bird density through the entire range for Grasshopper Sparrows, Dickcissels, and Lark Buntings, and in the High Plains for Western Meadowlarks. Percent woodland had negative effects on Western Meadowlarks in the Smoky Hills, whereas percent cropland had negative effects on Eastern Meadowlarks statewide. CRP positively affected abundance of four of our species, whereas percent cropland and woodland negatively affected others. Thus, the amount of set-aside lands enrolled in SAFE could be important for grassland bird populations. SAFE and CRP supported equal numbers of Northern Bobwhites and Ring-necked Pheasants, suggesting SAFE provides benefits for target species of upland gamebirds.
Keywords: Conservation Reserve Program; Grassland birds; Upland game birds; State Acres for Wildlife Enhancement; Ecology (0329); Wildlife Management (0286)